IL12B SNPs and copy number variation in IL23R gene associated with susceptibility to leprosy. Issue 1 (13th December 2012) - Ali, Shafat; Srivastava, Amit Kumar; Chopra, Rupali; Aggarwal, Shweta; Garg, Vijay Kumar; Bhattacharya, Sambit Nath; Bamezai, Rameshwar Nath Koul
Abstract : Background: Genome-wide studies have identified both human leucocyte antigen (HLA) and non-HLA regions in association with leprosy. Involvement of novel functional loci within these regions has been proposed by us earlier. Methods: We investigated the role of 23 single nucleotide polymorphisms (SNPs) in IL12B and IL12RB2 in a total of 2345 individuals from India, using MassArray platform, along with the copy number variations in IL23R, IL12RB2 and IL10 genes in a representative set of 257 individuals, using real-time PCR. Results: SNP rs2853694 in IL12B gene (AA vs AC+CC, p=2.6E-04, OR=1.42 (1.17–1.70)) showed an association with leprosy. Pairwise interaction analysis followed by combined analysis of multiple SNPs identified that IL12B, TNF and BTNL2-DRA inter-genic SNPs provided a major risk towards leprosy (p=2.6E-08, OR=3.94 (2.43–6.38)), showing a further increase (p=3.6E-14) for combined risk genotype interactions. On the other hand, IL12B, BAT1, NFKBIL1 and LTA SNPs together showed a disposition towards protection (p=0.000011, OR=0.32 (0.19–0.53)) with a further increase (p=6.38E-10) for combined protective genotype-interactions. Copy number variation analysis showed an increased copy number of the IL23R gene (PB=36.4%, controls=20.2%; p=0.026) associated with the pauci-bacillary form of leprosy, which correlated with a trend towards enhanced expression in memory T cells in a preliminary observation. Conclusions: The observations made here highlight the importance of interaction between specific genetic backgrounds of immune response related genes in the outcome of Mycobacterium leprae infection.